My sister's keeper : a novel - Picoult, Jodi, 1966- (New York : Washington Square Press, 2005)
Thirteen-year-old Anna, conceived specifically to provide blood and bone marrow for her sister Kate who was diagnosed with a rare form of leukemia at the age of two, decides to sue her parents for control of her body when her mother wants her to donate a kidney to Kate.
Originally published: New York : Atria Books, 2004.
School Library Journal
Wilson's Fiction
Wilson's Senior High School
Booklist starred, January 2004
Kirkus Review, January 2004
Keywords: Donation of organs, tissues, etc. -- Fiction; Leukemia -- Patients -- Fiction; Mothers and daughters -- Fiction; Organ donors -- Fiction; Sick children -- Fiction; Sisters -- Fiction; Teenage girls -- Fiction; Children -- Fiction; Domestic fiction; Donation of organs, tissues, etc -- Fiction; Girls -- Fiction; Leukemia -- Patients -- Fiction; Mother-daughter relationship -- Fiction; Teenagers -- Fiction; Domestic fiction